Dual-Mode Sensor with Saturated Mechanochromic Structural Color Enhanced by Black Conductive Hydrogel for Interactive Rehabilitation Monitoring - Sun, Zhiyuan; Yu, Binhong; Dong, Chao; Yu, Chengjun; Sheng, Lianghe; Cui, Zhe; Liu, Yaming; Lu, Zhenni; Chen, Bingda; Xie, Daixi; Huang, Zhandong; Zeng, Songshan; et al. (Nano-Micro Letters, 2026)
Flexible and wearable sensors offer immense potential for rehabilitation medicine, but most rely solely on electrical signals, lacking real-time visual feedback and limiting trainee’s interactivity. Inspired by the structural coloration of Cyanocitta stelleri feathers, we developed a dual-mode sensor by utilizing black conductive polymer hydrogel (CPH)-enhanced structural color strategy. This sensor integrates a hydroxypropyl cellulose (HPC)-based structural color interface with a designed CPH sensing component. Highly visible light-absorbing CPH (absorption rate > 88%) serves as the critical substrate for enhancing structural color performance. By absorbing incoherent scattered light and suppressing background interference, it significantly enhances the saturation of structural color, thereby achieving a high contrast index of 4.92. Unlike the faint and hardly visible structural colors on non-black substrates, the HPC on CPH displays vivid, highly perceptible colors and desirable mechanochromic behavior. Moreover, the CPH acts as a flexible sensing element, fortified by hydrogen and coordination bond networks, and exhibits exceptional electromechanical properties, including 867.1 kPa tensile strength, strain sensitivity (gauge factor of 4.24), and outstanding durability (over 4400 cycles). Compared to traditional single-mode sensors, the integrated sensor provides real-time visual and digital dual feedback, enhancing the accuracy and interactivity of rehabilitation assessments. This technology holds promise for advancing next-generation rehabilitation medicine. Highlights: 1 Mimicking Cyanocitta stelleri feathers, we developed a dual-mode sensor with strain-sensing and mechanochromic functions by using black conductive polymer hydrogel (CPH) substrate to enhance hydroxypropyl cellulose’s structural color. 2 The synthesized CPH, with >88% visible-light absorption, enhances color saturation by absorbing scattered light and suppressing background interference, enabling vivid mechanochromism. Fortified by noncovalent bonds, it also functions as a robust, sensitive sensor. 3 Unlike traditional single-mode sensors, this integrated sensor offers real-time visual and digital feedback, improving rehabilitation assessment accuracy and interactivity.